Telling the Truth…With Kindness: Retrospective Evaluation of 12 Years of Activity of a Support Group for Children and Their Parents With Cancer. Issue 2 (March 2016) - Landry-Dattée, Nicole; Boinon, Diane; Roig, Gaelle; Bouregba, Alain; Delaigue-Cosset, Marie-France; Dauchy, Sarah
Abstract : Background: Cancer in a parent can have harmful effects on a child's ability to cope with the situation, in particular if communication about the disease is limited. Objective: The aim was to evaluate whether the parent-child group run by a psychoanalyst and a doctor at the hospital helps facilitate communication about the disease with a child and helps to sooth the child and his/her symptoms. Methods: This qualitative retrospective study conducted among 61 families (71 adults, 19 children) using semidirected interviews made it possible to identify the expectations and benefits perceived by the parents and children. Results: The main expectations of the parents were to meet professionals who would help them to speak about the disease and to help the children understand it better in order to reduce their symptoms. The parents' expectations were largely satisfied. As far as the children are concerned, they expressed more benefits (better understanding of the disease, reduction of symptoms, meeting similar others) than expectations. Conclusions: The group is a resource that helps both parents and children. Meeting similar others made it possible to justify each participant's own experiences and promote better communication during the continued course of the disease. Implications for Practice: The benefits brought about by this group testify to the need to offer such support to a greater number of parents with cancer. Improvements to the way in which the group is organized are discussed.